1992
DOI: 10.1002/pola.1992.080301104
|View full text |Cite
|
Sign up to set email alerts
|

Free‐radical homopolymerization and copolymerization of ethyl α‐hydroxymethylacrylate in tetrahydrofuran

Abstract: SYNOPSISEthyl a-hydroxymethylacrylate ( EHMA) was polymerized in a 3 mol/L tetrahydrofuran solution at 50°C, using 2-2' azobisisobutyronitrile as initiator. The kinetic behavior indicates a higher polymerization rate for EHMA than for methyl methacrylate (MMA) . Copolymerization reaction between MMA and EHMA, under the same experimental conditions, was carried out and values of r M M A = 1.264 and r E H M A = 1.285 were found for the reactivity ratios. The comparison of triad sequences as determined from Berno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Furthermore, acrylates, having capto‐substituents, produce more stable propagating radicals as compared with allyl radicals and therefore, the propagation reaction is more exothermic in the case of acrylates 7, 23. Insertion of a heteroatom on the methylene group has a positive effect on the polymerizability of the monomer 13–17. Wong and Radom 8 have reported that large substituents would not affect the maximum overlap between the unpaired electron of the propagating radical and the unoccupied π orbitals of the double bond.…”
Section: Mechanistic Overview Of Free Radical Polymerization Of Acrylmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, acrylates, having capto‐substituents, produce more stable propagating radicals as compared with allyl radicals and therefore, the propagation reaction is more exothermic in the case of acrylates 7, 23. Insertion of a heteroatom on the methylene group has a positive effect on the polymerizability of the monomer 13–17. Wong and Radom 8 have reported that large substituents would not affect the maximum overlap between the unpaired electron of the propagating radical and the unoccupied π orbitals of the double bond.…”
Section: Mechanistic Overview Of Free Radical Polymerization Of Acrylmentioning
confidence: 99%
“…Thus, the k p / k 1/2ct ratio has been considered as a descriptor for the polymerizability behavior of the monomers in every group. Values of k p / k 1/2ct for the same reaction conditions have been used to analyze the kinetic behavior of acrylic monomers 13, 25.…”
Section: Rate Of Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A search of literature reveals that N-VP has been copolymerized with cyclohexyl acrylate using BPO [2] as initiator, maleic anhydride and maleimide initiated by laser rays [3] , monoalkyl Itaconate initiated by AIBN [4] . MMA have been copolymerized with different monomers [5,6] , initiated by conventional initiators as well as ylides [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been wide exploraethylenes such as methyl methacrylate, vinylitions about its synthesis, polymerization, and dene vinyl acetate, and styrene, [2][3][4][5][6][7][8][9] and in all cases copolymerization with styrene, methyl methacry-MI and its comonomers readily underwent therlate, and 2-vinyl-4,4-dimethylazlactone. [17][18][19][20][21][22][23][24] Because of the presence of the hydroxyl group, EHMA has been widely used as a new crosslink-example, EHMA has been utilized to improve the mechanical properties of wood 24 ; the thermal properties of 2-vinyl-4,4 -dimethylazlactone-EHMA copolymers have been studied to evaluate the stability and crosslinking activity of various functional groups in polymers.…”
Section: Introductionmentioning
confidence: 99%